Safety and Immunogenicity of a Human Epidermal Growth Factor Receptor 1 (HER1)-Based Vaccine in Prostate Castration-Resistant Carcinoma Patients: A Dose-Escalation Phase I Study Trial - Iraida Caballero; Lazaro E. Aira; Anabel Lavastida; Xitlally Popa; Javier Rivero; Joaquín González; Mónica Mesa; Narjara González; Kelly Coba; Patricia Lorenzo-Luaces; Barbara Wilkinson; Yuliannis Santiesteban; et al. (Frontiers Media S.A., 2017)
Metastatic castration-resistant prostate cancer (CRPC) remains incurable due to the lack of effective therapies. Activation of the human epidermal growth factor receptor 1 (HER1) in prostate cancer contributes to metastatic progression as well as to disease relapse. Here, we determined the toxicity and immunogenicity of a HER1-based cancer vaccine in CRPC patients included in a phase I clinical trial. CRPC patients (n = 24) were intramuscularly vaccinated with HER1 vaccine consisting of the extracellular domain of HER1 molecule (ECD) and very small size proteoliposome from Neisseria meningitidis (VSSP) and Montanide ISA-51 VG as adjuvants. Patients were included in five groups according to the vaccine dose (100, 200, 400, 600, and 800 μg). The primary endpoints were safety and immunogenicity. The anti-HER1 antibodies were measured by an ELISA, the recognition of an HER1 positive tumor cell line and the inhibition of HER1 phosphorylation by sera were determined by flow cytometry and western blot analysis, respectively. The HER1-specific T cell response was assessed by determination of IFN-γ-producing T cells using ELISpot assay. The vaccine was well tolerated. No grade III or IV adverse events were reported. High titers of anti-HER1 antibodies were observed in most of the evaluated patients. There were no significant differences regarding the geometric means of the anti-HER1 titers among the dose groups except the group of 100 μg in which antibody titers were significantly lower. A Th1-type IgG subclasses pattern was predominant in most patients. Only patients receiving the higher doses of vaccine showed significant tumor cell recognition and HER1 phosphorylation inhibition by hyperimmune sera. Forty two percent of the patients showed a specific T cell response against HER1 peptides pool in post-treatment samples. There was a trend toward survival benefit in those patients showing high anti-HER1 specific antibody titers and a significant association between cellular immune response and clinical outcome.